Event Studies of O+Density Variability Within Quiet‐Time Plasma Sheet. Issue 6 (18th June 2019) - Wang, Chih‐Ping; Fuselier, Stephen A.; Hairston, Marc; Zhang, Xiao‐jia; Zou, Shasha; Avanov, Levon A.; Strangeway, Robert J.; Ahmadi, Narges; Bortnik, Jacob
Abstract: To understand the variations of the O + ions in the quiet‐time plasma sheet between the regions of cold‐dense plasma sheet (CDPS) and hot plasma sheet (HPS), we conduct three event studies. These studies investigate the O + densities in the two regions and how they are correlated with the strength of two magnetospheric sources important to ion outflows: the soft electron flux and Poynting flux toward the ionosphere. The CDPS is characterized by two‐component ions (one hot component mixed with one cold component), while the HPS ions consist of only one single hot component. Comparing the O + density between the CDPS and HPS of the same event, the average CDPS O + density was higher by a factor of 2–5. Compared to the HPS, the soft electron flux source within the CDPS was higher, consistent with the fact that the soft electron precipitation and O + upward number fluxes observed in the ionosphere were also higher within the CDPS. In the plasma sheet, broadband ultralow‐frequency electric and magnetic field waves with the characteristics of kinetic Alfvén waves were often more intense within the CDPS, providing a stronger Poynting flux source. In addition, electron resonant interaction with kinetic Alfvén waves results in acceleration along the magnetic fields and, thus, may drive the observed soft electron precipitation. These correlations suggest that the higher soft electron precipitation and Poynting flux coming from the magnetospheric CDPS likely produce larger ionospheric O + outflows back to the magnetosphere, thus resulting in the higher O + density within the CDPS. Key Points: O + densities in cold‐dense plasma sheet in the three quiet‐time events were higher than those in hot plasma sheet by a factor of 2‐5 Higher soft electron fluxes in the magnetosphere and soft electron precipitation in the ionosphere in cold‐dense than hot plasma sheet More intense kinetic Alfven waves within the CDPS, providing stronger Poynting flux downward to the ionosphere